Transcriptomic Analysis Reveals the Regulatory Networks and Hub Genes Controlling the Unsaturated Fatty Acid Contents of Developing Seed in Soybean - Liu, Junqi; Dong, Liang; Duan, Runqing; Hu, Li; Zhao, Yinyue; Zhang, Liang; Wang, Xianzhi (Frontiers in Plant Science, 2022)
Soybean (Glycine max (L.) Merr.) is one of the most important crops which produces about 25% of the world’s edible oil. The nutritional value of soybean oil depends mostly on the relative contents of three unsaturated fatty acids, i.e., oleic acid, linoleic acid and linolenic acid. However, the biosynthetic mechanism of unsaturated fatty acids remains largely unknown, and there are few studies on RNA-Seq analysis of developing seeds. To identify candidate genes and related pathways involved in the regulation of unsaturated fatty acid contents during seed development in soybean, two soybean lines with different unsaturated fatty acid profiles were selected from 314 cultivars and landraces originated from Southern China, and RNA-seq analysis were performed in soybean seeds at three developmental stages. Using GO and KEGG enrichment analysis, a series of genes and pathways related to fatty acid metabolism were identified, and DAF 40 was found to be the crucial period in the formation of unsaturated fatty acid profiles. Further, weighted gene co-expression network analysis identified three modules with 6 genes whose functions were highly associated with the contents of oleic and linoleic acid. The detailed functional investigation of the networks and hub genes could further improve the understanding of the underlying molecular mechanism of unsaturated fatty acid contents, and might provide some ideas for the improvement of fatty acids profiles in soybean.